Identifikasi Karakteristik Kualitas Menggunakan Pendekatan TCM Berbasis Kebutuhan Fungsional - Denni Aldi Ramadhani; Umi Laili Yuhana (Fakultas Teknik, Universitas Brawijaya, 2015)
Defining quality requirements is an important activity in the development of software because quality requirements describe how well the software can be implemented. In this study will propose an approach to make improvements the specification of quality characteristics software using a spectrum analysis by utilizing the TCM (Term-Characteristic Mapping) method, in this method also utilize algorithms RabinKarp used to perform mapping between the list of term with functional requirements written in the software requirement specification documents. for testing phase its used 167 term of quality and 22 subcategories quality characteristics and uses two software requirement specification documents that will appear the quality characteristics. Results from this study is a list of quality characteristics that appear along with the value of its appearance in the functional requirements are analyzed.Keywords—quality requirements, TCM, RabinKarp, quality characteristics